Implementing inclusive education issues in bridging the policy-practice gap - Watkins, Amanda, active 2016.; Meijer, Cor J. W. (Bingley, U.K. : Emerald, 2016)
The volume will provide an examination of issues around how policy for inclusive education can be implemented in practice. In relation to different thematic policy areas considered in each chapter these questions will be considered: What are the main policy issues for inclusive education? What recommendations are there for addressing these issues? What are the difficulties in implementing these recommendations? How can these difficulties be overcome? Overall conclusions will focus on lessons learnt for supporting the implementation of policy for inclusive education and bridging the policy-practice gap.
Changing conceptions of inclusion underpinning education policy / Cor Meijer, Amanda Watkins -- Ensuring a strong start for all children: inclusive early childhood education and care / Paul Bartolo, Eva Bjo<U+0308>rck-A<U+030a>kesson, Climent Gine<U+0301>, Mary Kyriazopoulou -- Financing inclusive education: policy challenges, issues and trends / Serge Ebersold, Cor Meijer -- Educating all teachers for inclusion / Amanda Watkins, Annet De Vroey, Simoni Symeonidou -- Inclusive vocational education and training (VET) - policy and practice / Edgar Pereira, Mary Kyriazopoulou, Harald Weber -- How can education systems support all learners? tipping-point leadership focused on cultural change and inclusive capability / Per Skoglund, Hans Sta<U+0308>cker -- Multicultural diversity and special educational needs / Geoff Lindsay, Sonali Shah, Mary Kyriazopoulou -- ICT as a tool for supporting inclusive learning opportunities / Marcella Turner-Cmuchal, Stuart Aitken -- Addressing the challenges of raising achievement for all / Verity Donnelly, Finn O<U+0301> Murchu<U+0301>, Wiltrud Thies -- Inclusive assessments: issues and challenges for policy and practice / Anthoula Kefallinou, Verity Donnelly -- Efficiency, effectiveness and equity within inclusive education systems / Amanda Watkins, Serge Ebersold -- Young voices on inclusive education / Victoria Soriano.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Education -- Special Education -- General; Teaching of specific groups & persons with special educational needs; Inclusive education